PENGARUH RISIKO KREDIT, RISIKO SOLVABILITAS DAN KUALITAS AUDIT TERHADAP PROFITABILITAS PERUSAHAAN SERTA IMPLIKASINYA TERHADAP KUALITAS LABA - Pardomuan Ritonga (Universitas Multimedia Nusantara, 2020)
Abstract- This research aims to analyzethe influence of financial risk i.e. credit and solvency risk as long as audit quality on the firm's profitability and implications with earnings quality. This type of research is quantitative. The research population is sub-sectors of general insurance listed in the Indonesia Stock Exchange in 2014-2018. The sampling method using purposive sampling technique is counted 10 companies. The method of analysis using linear regression analysis and sobel test. These results indicate that financial risk has significant effect simultaneously on the profitability of firms as long as financial risk and audit quality has no significant effect simultaneously on the earnings quality. The partial test results showed that solvency risk and audit quality have a negative effect while credit risk has no significant effect to the profitability of firms. However, credit and solvency risk as long as audit quality have no indirect effect to the earnings quality through profitability of firms. Keywords: solvency risk, profitability of firms, earnings quality value